A multidisciplinary policy approach to food and agricultural biosecurity and defense - McClaskey, Jackie M. (Kansas State University, 2014)
The U.S. agriculture industry is diverse and dynamic, plays a vital role in the nation’s economy, and serves as a critical component in providing the global food supply. Agriculture has and always will be susceptible to threats such as pests, disease, and weather, but it is also threatened by intentional acts of agroterrorism. One specific area of concern is foreign animal diseases (FAD) and the danger these diseases create for the U.S. livestock industry. Whether a disease outbreak is intentional or accidental, it could devastate animal agriculture and the food infrastructure and have a lasting impact on state, national, and global economies. One of the most economically devastating diseases that raise fear and anxiety in the livestock industry is foot and mouth disease (FMD). A number of administrative, regulatory, and legislative actions have been implemented at state and federal levels designed to protect the agriculture industry and to prevent, prepare for, and respond to an accidental or intentional introduction of an FAD. However, the consistency, clarity, and long-term commitment of these policy approaches remains in question. Effective policy decisions require a multidisciplinary approach that consider and balance science, economics, social factors, and political realities. A significant number of policy analysis tools exist and have been applied to animal emergency scenarios but few actually address the complexity of these policy dilemmas and provide information to policymakers in a format designed to help them make better decisions. Policy development needs to take a more multidisciplinary approach and better tools are needed to help decision makers determine the best policy choices. This dissertation analyzes three FAD policy dilemmas: mass euthanasia and depopulation, carcass disposal, and vaccination. Policy tools are developed to address the multidisciplinary nature of these issues while providing the information necessary to decision makers in a simple and useful format.
Keywords: Agricultural policy; Foreign animal disease; Policy analysis; Agricultural biosecurity; Animal Sciences (0475); Economics, Agricultural (0503); Public Policy and Social Welfare (0630)